2008
DOI: 10.1371/journal.pone.0002804
|View full text |Cite|
|
Sign up to set email alerts
|

Dopamine Inhibits Mitochondrial Motility in Hippocampal Neurons

Abstract: BackgroundThe trafficking of mitochondria within neurons is a highly regulated process. In an earlier study, we found that serotonin (5-HT), acting through the 5-HT1A receptor subtype, promotes axonal transport of mitochondria in cultured hippocampal neurons by increasing Akt activity, and consequently decreasing glycogen synthase kinase (GSK3β) activity. This finding suggests a critical role for neuromodulators in the regulation of mitochondrial trafficking in neurons. In the present study, we investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 46 publications
4
40
0
Order By: Relevance
“…It has been reported that nerve growth factor (NGF) affects mitochondrial motility by its downstream phosphoinositide 3-kinase (PI3K) signaling pathway (8). Edelman and co-workers (9,10) have demonstrated that Akt-glycogen synthase kinase 3␤ (GSK3␤) is associated with axonal mitochondrial transport stimulated by serotonin and dopamine. Calcium has been demonstrated to be one of the critical factors that regulate mitochondrial transport (11)(12)(13).…”
mentioning
confidence: 99%
“…It has been reported that nerve growth factor (NGF) affects mitochondrial motility by its downstream phosphoinositide 3-kinase (PI3K) signaling pathway (8). Edelman and co-workers (9,10) have demonstrated that Akt-glycogen synthase kinase 3␤ (GSK3␤) is associated with axonal mitochondrial transport stimulated by serotonin and dopamine. Calcium has been demonstrated to be one of the critical factors that regulate mitochondrial transport (11)(12)(13).…”
mentioning
confidence: 99%
“…Dopamine also inhibited mitochondrial complex I-driven respiration when added short-term or long-term to the medium of cultured SH-SY5Y cells [213]. Moreover, administration of exogenous dopamine to hippocampal neurons blocked the trafficking of mitochondria [214]. Finally, dopamine has been shown to interfere with CMA [215] and to promote autophagy-dependent cell death via upregulation of asynuclein expression [216].…”
Section: Effects Of Pink1 Ablation On Mitochondrial Morphologymentioning
confidence: 99%
“…Actually, activation of dopamine D2 receptors in mutant huntingtin striatal neurons alters mitochondrial function by down-regulating mitochondrial complex II expression [18] while mitochondrial axonal transport can be regulated by integration of the opposite effects of D1R and D2R activation [47]. Notably, there is no data on the potential role of dopamine receptors in mitochondrial fission-fusion events.…”
Section: Accepted Manuscriptmentioning
confidence: 99%